Further development of expert system for welding personnel qualification : ISO 9606-1 - Koo, Wei Chean (2019)
Welding is a significant process which involves joining materials together and is frequently applied in many areas. Many of its applications start off from simple products such as tray tables which can be constructed into complex transportation like huge vessels. In our modern society, welding has advanced with technology. High demand products generally will not be an issue as current welding processes are able to cope with the speed of the demand. Nowadays people are concerned about the reliability and quality of the product. Hence, it is essential to place emphasis in the quality product controlling during the manufacturing process. Any defect found during the process will be rejected and material immediately. In order to maintain its quality and producing less rejects or waste, standards are implemented to ensure that quality of the product were not compromised. Therefore, the world organization has implemented this International Standard Organization (ISO). There are many standards listed under ISO. However, the main study will only be focusing on ISO 9606-1 (Qualification testing of welder – Fusion Welding). This document has multiple regulations that are too complex for a welder or examiner to follow closely. Therefore, there is a need to come out with an expert system to solve the problem. In this report, a straight-forward application named “Eazy Weld” which is easy to use and understand will be discussed.